EFL Learners’ Speaking Anxiety and English Speaking Ability - Handayani, Yeni Rina; Ngadiman, Agustinus (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2018)
The aim of this study was to investigate the correlation between speaking anxiety and presentational English speaking ability. The subjects were the eleven graders of Senior High School in Surabaya. It consisted of 457 students whose age ranged between sixteen to seventeen years old. They came from social and science classes which were divided into seven science classes and five social classes. The result of the study revealed that there was a negative correlation between speaking anxiety and presentational English speaking ability. And there was also a negative correlation between speaking anxiety and each of speaking ability subskills.